OASIS evaluation of the French laboratory diagnostic surveillance system: right people, right techniques but imperfect use - Chikh, Maïssane; Ngwa-Mbot, David; Morignat, Eric; Memeteau, Sophie; Amat, Jean-Philippe (Frontiers in Veterinary Science, 2025)
Laboratory diagnostic surveillance is the surveillance of incidents and the risk of incidents, resulting from the use of diagnostic tests. The role of this surveillance is to detect the potential mistakes in laboratories’ analytic methods and defects in diagnostic tests. We assessed the diagnostic surveillance system dedicated to five cattle diseases in France: infectious bovine rhinotracheitis (IBR), brucellosis, hypodermosis, bovine viral diarrhea (BVD) and enzootic bovine leukosis, using OASIS, a method developed for the assessment of surveillance systems. Information regarding the organization and functioning was collected during semi-structured interviews with actors taking part in the laboratory diagnostic surveillance system, including staff at national reference laboratories, diagnosis laboratories, veterinarians, diagnostic test manufacturers, cattle owners’ association and veterinary services. A scoring grid of 78 criteria was completed, based on the insights collected during the interviews. This scoring was then used for the calculation of seven surveillance critical control points based on the hazard analysis of critical control points approach and of ten quality attributes of the system. Key performance factors included: good technical management of laboratories, a monitoring of the performance of diagnostic tests by laboratories (intern control charts) and a good level of expertise for all actors. The areas of improvement were related to the lack of formalized bodies (steering committee, scientific and technical committee, coordinators, etc.), the lack of reporting guidelines, insufficient feedback to actors (regarding incidents and functioning of the system), and the absence of a definition of a case in laboratory diagnostic surveillance. In order to address these flaws, we recommend a new organization. Other main proposals for improvement included: establishing guidelines for reporting and investigating; raising the awareness of the actors concerning laboratory diagnostic surveillance; and establishing feedback meetings focused on the events of laboratory diagnostic surveillance. Such an evaluation should be conducted for other diseases and in other countries. It would be useful to share the results, especially within Europe, to implement improvements at the European level.